Principals and technology use - Afshari, Mojgan; Abu Bakar, Kamariah; Wong, Su Luan; Afshari, Marjan (WSEAS Press, 2010)
This study identified the extent to which Iranian secondary school principals used computers and investigated the relationship between computer use and three independent variables: computer attributes, computer access, and personal characteristics (including gender, age, administrative experience, type of the school, and computer training background). The findings suggest that principals spend a few times a week working on their computers. Also, factors such as high level of computer access and strong perceptions of the attributes of ICT contribute significantly to the computer use by principals. It can be concluded that principals must embrace the movement and utilize technology themselves if they expect the staff to adapt and use technology without resistance. This will make the teachers feel more comfortable knowing that the principal is competent and willing to utilize technology him or herself. Therefore, necessary training and resources should be provided for principals to effectively use technologies in the performance of their work responsibilities.